2016
DOI: 10.11648/j.ijalt.20160203.11
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Mistakes in College English Writing: Problem Analysis, Reasons and Solutions

Abstract: Abstract:In our modern society, English is used as an international language and communication tool, and it plays a more and more important role in the world. University students are regarded as the pioneers of modern information and it is self-evident that English is one of the important channels to get information. However, from the four basic skills of English --listening, speaking, reading and writing, writing needs the most comprehensive knowledge, the strongest application, and the most difficult trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…In order to answer the first research question of the study which states "What are the most frequent grammatical errors in the writings of students in Alhusssein Bin Talal University" the means and standard deviations of the grammatical errors were done and ordered as shown in Table 2. The results in Table 2 shows that the most frequent grammatical error was with the verb tense on a mean of (3.75), followed by errors in the article on a mean of (3.62), wrong word order on a mean of (3.57), noun ending on a mean of (3.40) and least was sentence structure on a mean of (3.39).This agrees with a study done by Li et al (2016) on Grammatical Mistakes in College English Writing: Problem Analysis, Reasons and Solutions, and they found that students make mistakes in verbs, nouns, articles, sentence structure and more. It also agrees with the study done by Leman (2014) on finding the Common grammatical errors in students writing .his results showed that students make mistakes in word order, article, subject very agreement, verb tense and more.…”
Section: Resultssupporting
confidence: 89%
“…In order to answer the first research question of the study which states "What are the most frequent grammatical errors in the writings of students in Alhusssein Bin Talal University" the means and standard deviations of the grammatical errors were done and ordered as shown in Table 2. The results in Table 2 shows that the most frequent grammatical error was with the verb tense on a mean of (3.75), followed by errors in the article on a mean of (3.62), wrong word order on a mean of (3.57), noun ending on a mean of (3.40) and least was sentence structure on a mean of (3.39).This agrees with a study done by Li et al (2016) on Grammatical Mistakes in College English Writing: Problem Analysis, Reasons and Solutions, and they found that students make mistakes in verbs, nouns, articles, sentence structure and more. It also agrees with the study done by Leman (2014) on finding the Common grammatical errors in students writing .his results showed that students make mistakes in word order, article, subject very agreement, verb tense and more.…”
Section: Resultssupporting
confidence: 89%
“…Next finding shows that teacher's feedback in English writing helps the improvement of students' writing skill and that finding is similar to that of Richard's (2014). The results reveal that there are a lot of grammatical mistakes in students' writing and that finding is similar to the finding of Fengjie et al (2016). The next finding indicates that it is a time consuming process and semester is short.…”
Section: Discussionsupporting
confidence: 73%
“…The result is consistent with Li et al (2016) when students tended not to use coordinating conjunctions to connect sentences, causing run-on sentences, or when they could not use subordinating connectors correctly, leading to sentence fragments (Singh et al, 2017). Hence, English teachers should rst have students write independent clauses or complete simple sentences.…”
Section: Discussionsupporting
confidence: 56%